HISTOLOGICAL FEATURES OF ETHAMBUTOL INDUCED MICE EYES: A PRE- EXPERIMENTAL STUDY ON TOXIC OPTIC NEUROPATHY CASE: Oral Presentation - Experimental Study - Ophthalmologist - BATARI TODJA UMAR; Itzar Chaidir Islam (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Toxic Optic Neuropathy (TON) is a visual disease caused by toxic substances damaging the optic nerve. It can be caused by inflammation, infection, or long-term drug use. Over 10% of ethambutol- treated optic neuropathy patients developed major complications. Cellular changes should be observed histologically. This study examines ethambutol-induced mice's eye histology in the fibrous, vasculous, nervous tunica, optical media, and optic nerve tissue. Methods : This pre-experimental study used 20 eyes of 10 white mice aged 1-2 weeks weighing 50-65 grams. Group 1 consisted of healthy mice without therapy and group 2 received 35 mg/kgBW/day of ethambutol for 60 days. (group 2). Hematoxylin eosin staining was used to observe binocular experimental animal eyes after enucleation. All measurements used Olympus® CX-20 microscope with 40x objective resolution. Results : The average thickness of the cornea was 72.238 ± 10.542 and 60.572 ± 10.25, while the sclera was 336.533±40.851 μm and 331.339±34.219 μm. In groups 1 and 2, no significant changes were foundin the cell layer morphology of both tissues (p > 0.05). Iris, ciliary body, and choroid were observedin the tunica vasculosa. Groups 1 and 2 had eye and ciliary body lengths of 595.148±137.805 μm and 497.705±213.866 μm, respectively, and choroid thicknesses of 161.369±37.925 and 162.605±25.160 (p>0.05). Group 1 had 402.268±55.666 μm retinal thickness in the tunica nervosa, while group 2 had 399.854±27.585 (p>0.05). Conclusion : Ethambutol-induced and normal experimental animals had substantial histological differences in optic nerve thickness, but no significant difference in the other ocular structures.